Profile of the export and import of essential oils in Brazil, between 2020 and 2021, and the predominance of essential oil from Melaleuca alternifolia in Paraná (Research, Society and Development, 2021)
Essential oils represent, along with their active ingredients, an important potential for treatments with medicinal action aimed at the world population, with products in the vast majority with their scientifically proven actions, highlighting the value of improving discoveries related to these components. In this study, a data survey was carried out by performing an economic analysis equivalent to the export and import of essential oils in Brazil and in the state of Paraná. An evaluation of which oil is produced by most producers in the state has also been carried out. The result was the oil from Melaleuca alternifolia, commonly known as melaleuca, produced as tea tree. This oil comes from Australia and comes from various functionalities such as antimicrobial for the most part, antifungal and healing, having its therapeutic applications in wide areas, which shows that this is a field that still has a lot to offer to the national and international market.